(untitled) (Asian Journal of Social Science Studies, 2022)
Basic research is the source of the whole scientific system. How to improve the efficiency of diversified investment in basic research is of special significance to the development of basic research in China. Therefore, this paper combines China’s basic research investment dilemma, draws on the excellent experience of the United States, Japan and other advanced countries, further develops the fund-raising channels for basic research, guides social capital to fund basic research in the form of donations or the establishment of foundations, etc., and promotes the high-quality development of basic research in China.